The phytohormone indole-3-acetic acid induces quorum sensing signal DSF turnover via a positive feedback biosynthetic loop in the phytopathogen Xanthomonas campestris - Si-Nan Li; Minglei Zhang; Ying Cui; Lin Li; Chitti Thawai; Lian Jiang; Donglan Tian; Yu-Cheng Gu; Ya‐Wen He; Lian Zhou; Kai Song (Stress Biology, 2026)
ATP synthases and a resistance-nodulation-cell division (RND)-family efflux pump HepABCD to induce a pH-dependent DSF turnover. Moreover, IAA downregulated another RND family efflux pump IaepABCDE to induce a pH-independent DSF turnover. Finally, the IAA-regulated gene clusters were transcribed during the XC1 infection of cabbage. Collectively, these findings reveal a previously unrecognized role of IAA in modulating bacterial QS, underscoring the importance of IAA in the molecular dialogue between the pathogen and its host.
Keywords: Bacterial biofilms and quorum sensing; Plant-Microbe Interactions and Immunity; Plant Pathogenic Bacteria Studies